Is polio eradication possible? - Ruszel, Kinga; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2020)
Poliomyelitis is called childhood paralysis, anterior horn inflammation of the spinal cord and Heine-Medin disease. Poliomyelitis is caused by poliovirus. Infection spreads through ingestion of objects and foodstuffs contaminated with pharyngeal secretions or faeces. The virus multiplies in the intestine, from where it can attack the nervous system and can cause paralysis that is often permanent. The initial symptoms of polio include fever, headache, vomiting, stiff neck, and pain in the extremities. Majority of cases is either completely asymptomatic or result in a mild disease typical of a generalized viral infection; Poliomyelitis paralysis occurs in 0.1–1% of infections. There is no cure for polio, it can only be prevented by immunization. In 1988, the World Health Assembly adopted a resolution that committed all countries to polio eradication by the year 2000. The aim of the review is to summarize data on the incidence of polio virus infection in recent years in the world. PubMed databases and statistics from the Centers for Disease Control and Prevention (CDC), Polio Global Eradication Initiative and world data from WHO websites were searched in July and August 2020. In PubMed we used any text and medical terms ‘polio’, ‘poliomyelitis’, ‘polio vaccine’. Twenty two publications were cited. In conclusion: Majority of the wold is free from polio. Polio still spreads in several countries. In a country which is not free of polio all residents and longterm visitors (> four weeks) of all ages, should receive a dose of bivalent oral poliovirus vaccine (bOPV) or inactivated poliovirus vaccine (IPV) between four weeks and 12 months prior to international travel. It can helps with restrict of transmission of polio outside the border.